Barriers to the implementation of Building Information Modelling (BIM) for facility management. (1st April 2022) - Durdyev, Serdar; Ashour, Mojtaba; Connelly, Scott; Mahdiyar, Amir
Abstract: Reportedly, the application of Building Information Modelling (BIM) as a collaborative methodology for the life-cycle management of a building has numerous benefits. Nevertheless, its adoption during the operational stage remains limited, and the New Zealand (NZ) built environment is no exception. The present study offers a prioritized list of barriers that are inhibiting industry-wide adoption of BIM during the facility management (FM) phase. Both BIM and FM contexts were first thoroughly reviewed to identify the potential barriers (26), which were then refined via semi-structured interviews with qualified experts representing industry and academia. The refined barriers (20) were then prioritized through a hybrid Parsimonious Fuzzy AHP approach. Despite the leadership of the decision-makers in promoting the use of BIM in all phases of the building life cycle, the cost-related barriers (both for BIM software/hardware and training) remain the most significant. Perhaps, as a result of this, lack of expertise and unfamiliarity with BIM associated technology is among the most inhibiting barriers, which also requires utmost attention. It can be concluded that the industry stakeholders need to commit additional resources to help overcome the barriers and enable a wider application of BIM for FM. Increased application of BIM for FM will have positive implications for the future of the FM industry and digital future of the built environment, which has been a national strategy. The results are believed to identify the most crucial barriers impeding technology supported change in FM practices. Highlights: Barriers to BIM implementation are identified and refined based on their relevance to NZ FM context. A novel fuzzy parsimonious AHP method is exploited. The weights of refined barriers to BIM implementation for FM are calculated. Cost and lack of BIM expertise are the most inhibiting barriers to wider implementation of BIM for FM.